Explanation of English verbal groups (Journal of Human Sciences, 2018)
This paper provides a detailed description and explanation of the English verbal group element and their systems in English language. First, we start by introducing the field of linguistics and syntactic studies with a brief outline of the relevant grammatical theories. The syntactic structure of certain verbal units will also be explained. Second, the predicator in terms of its role, position, characteristics and representatives will be considered and explained in terms of its syntactic relations. Third, the verbal group will be analysed in terms of its elements and expounded in relation to its syntactic systems. The goal of this paper is to provide a classification of the verbs and verbal group of English for readers of comparative linguistics. It details the issue of verbs so that it is understood in relation to analysis or comparison.